2006
DOI: 10.1002/cbic.200600339
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Ligands that Target Cells Displaying the αvβ3 Integrin

Abstract: Strategies to eliminate tumor cells have long been sought. We envisioned that a small molecule could be used to decorate the offending cells with immunogenic carbohydrates and evoke an immune response. To this end, we describe the synthesis of bifunctional ligands possessing two functional motifs: one binds a cell-surface protein and the other binds a naturally occurring human antibody. Our conjugates combine an RGD-based peptidomimetic, to target cells displaying the alpha v beta3 integrin, with the carbohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 126 publications
(104 reference statements)
1
80
0
Order By: Relevance
“…Recognition of host cell-surface antigens is an essential stage of any infection, colonization, and metastasis. Heterobifunctional inhibitors/mediators designed to recognize both cell-surface receptors and antibodies may target malignant B cells (26) or provide instant adaptation of the host immune system to a novel pathogen or toxin and buy necessary time for development of an efficient adaptive immune response in an immunologically naïve host (19,20). Multivalent supramolecular binding systems of the type described herein that can attract humoral or cellular components of the host immune system to the site of interaction have the potential to provide a first line of defense against a multitude of pathogenic organisms and malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of host cell-surface antigens is an essential stage of any infection, colonization, and metastasis. Heterobifunctional inhibitors/mediators designed to recognize both cell-surface receptors and antibodies may target malignant B cells (26) or provide instant adaptation of the host immune system to a novel pathogen or toxin and buy necessary time for development of an efficient adaptive immune response in an immunologically naïve host (19,20). Multivalent supramolecular binding systems of the type described herein that can attract humoral or cellular components of the host immune system to the site of interaction have the potential to provide a first line of defense against a multitude of pathogenic organisms and malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Heterobifunctional ligand-adaptors designed to bind both a target protein and an endogenous multivalent protein template with matching spatial arrangement of binding sites are able to mediate highly stable supramolecular assemblies (15)(16)(17)(18)(19)(20)(21). Recently, it was demonstrated that a heterobifunctional ligand can be designed to mediate the face-to-face interaction between bacterial AB 5 toxins and HuSAP (15,16,21), which leads to the occlusion of all of the carbohydrate-binding sites in the Stx1 or cholera toxin B pentamers, thereby preventing the interaction between the toxin and its glycolipid receptor on host cells.…”
mentioning
confidence: 99%
“…In contrast to biologybased vaccine approaches, which aim to educate the immune system to create immunoglobulins of a defined specificity, the chemistry-based vaccine approach described here provides the immune system with defined specificities by coupling the biology-based induction of programmable immunoglobulins with ligand design and covalent self-assembly. The earliest related chemistry-based vaccine strategies were aimed at redirecting common natural antibody specificities such as anti-dinitrophenyl and anti-␣-galactosyl antibodies to targets by decorating them with highly immunogenic antigens like dinitrobenzene and galactosyl-␣ (1-3)galactose (26)(27)(28)(29). Such natural antibody specificities are typically of low affinity and to the best of our knowledge no such study has reported efficacy in a disease model.…”
Section: Discussionmentioning
confidence: 99%
“…Many cell surface receptors including folate receptor (161,162), transferrin receptor (163), interleukin-1 (IL-1) receptor (164), epidermal growth factor (EGF) receptor (165), endogenous G-protein coupled receptor (166,167), vasoactive intestinal receptor (gastrointestinal tumor) (168), gastrin and cholecystokinin/gastrin (thyroid and prostate tumor) receptors (169,170), neurotensin receptor (171), vascular endothelial growth factor receptor (172), fibroblast growth factor receptor (173), and α ν β 3 integrin-binding receptors (158,174,175) have been explored for selective targeting of drug-loaded NPs to tumor cells.…”
Section: Tumor Deliverymentioning
confidence: 99%